Analisis Tingkat Kesehatan Bank dan Potensi Kebangkrutan Menggunakan Metode CAMEL dan Z-Score pada Bank BJB Syariah Periode 2016-2020 - Nabilatul Amaliyah; Muhammad Iqbal Surya Pratikto (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
Banks are institutions that manage public funds, so it is very important to maintain good conditions. This can be maintained by analyzing the soundness of the bank from the results of the calculation of the ratios using a predetermined method. The research was conducted with the aim of knowing the condition of the bank's soundness level and the potential for bankruptcy that might occur in BJB Syariah for the 2016-2020 period. The study was conducted using a quantitative descriptive method with the type of data used is secondary data in the form of annual reports and BJB Syariah year-end quarterly reports 2016-2020, using bank soundness analysis techniques with the CAMEL method and potential bankruptcy analysis techniques with the Modified Altman Z-Score equation model. The results of the research conducted indicate that the soundness level of the BJB Syariah bank in 2016-2017 is in the PK-4 category or less healthy, in 2018-2019 it is in the PK-2 or healthy category, and in 2020 it is in the PK-3 category or quite healthy and the analysis of potential bankruptcy conducted in 2016-2020 did not detect any bankruptcy.